The Reconfiguration of Intra-Regional Trade in the EAEU Under Sanctions Against Russia - Khmeleva, Galina; Kurnikova, Marina; Chirkunova, Ekaterina (Bulletin of Yerevan University G: Economics, 2025)
The 2022 sanctions on Russia created a natural experiment testing the resilience of the Eurasian Economic Union. This paper investigates the transformative impact of these sanctions on the structure, volume, and logistics of intra-regional trade within the EAEU. It aims to identify the key adaptation mechanisms that ensured the bloc’s resilience and to analyze the reconfiguration of its internal economic landscape. Using 2021–2024 trade and logistics data, we document a stark divergence: while Russia’s and Belarus’s 2024 exports contracted to 80.2% and 20.0% of their 2021 levels, respectively, Armenia’s exports surged to 439.4%, with Kyrgyzstan and Kazakhstan also more than doubling. A granular analysis reveals profound structural shifts beneath these aggregates: EAEU imports consolidated around critical machinery and consumer goods, while exports underwent a pronounced shift towards a commodity-based economy, with the share of mineral fuels soaring from 44% to 62% of the total. This reorientation was enabled by a logistical pivot to road transport, which saw a 28% increase in freight turnover, and the emergence of vital hubs like Armenia. We argue that the EAEU’s pre-existing institutional architecture was critical for this adaptation, transforming into a vital buffer. While the sanctions were a primary catalyst, other global economic factors concurrently shaped these outcomes. The study offers global lessons on the diminishing returns of sanctions against integrated blocs and the newfound strategic agency of small economies in a fragmenting world.
Keywords: sanctions; Eurasian Economic Union; EAEU; regional integration; trade reconfiguration; economic resilience; logistics adaptation; import substitution; institutional resilience